2020
DOI: 10.1016/j.bcp.2019.113749
|View full text |Cite
|
Sign up to set email alerts
|

Intake of omega-3 formulation EPA:DHA 6:1 by old rats for 2 weeks improved endothelium-dependent relaxations and normalized the expression level of ACE/AT1R/NADPH oxidase and the formation of ROS in the mesenteric artery

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…On the contrary, supplementation with omega-3 fatty acids is reported not only to reduce arterial contraction [ 70 , 71 , 72 , 73 ], but also to improve endothelium-dependent relaxation [ 74 , 75 , 76 , 77 , 78 ]. Our results agree with those of Farooq et al, which show that omega-3 supplementation reverts the impairment of endothelium-dependent relaxation, the increase in angiotensin AT-1 receptor expression and the oxidative stress induced by aging in rat mesenteric arteries [ 79 ]. Thus, the beneficial effects an vascular function are most likely mediated by omega 3 PUFA, although the decrease in SFA may also be involved, since increased levels of SFA are reported to impair endothelium-dependent vasorelaxation in aging [ 80 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the contrary, supplementation with omega-3 fatty acids is reported not only to reduce arterial contraction [ 70 , 71 , 72 , 73 ], but also to improve endothelium-dependent relaxation [ 74 , 75 , 76 , 77 , 78 ]. Our results agree with those of Farooq et al, which show that omega-3 supplementation reverts the impairment of endothelium-dependent relaxation, the increase in angiotensin AT-1 receptor expression and the oxidative stress induced by aging in rat mesenteric arteries [ 79 ]. Thus, the beneficial effects an vascular function are most likely mediated by omega 3 PUFA, although the decrease in SFA may also be involved, since increased levels of SFA are reported to impair endothelium-dependent vasorelaxation in aging [ 80 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, decreased vascular inflammation and oxidative stress may be the mechanism by which the oil mixture treatment attenuates endothelial dysfunction in aged rats, as it significantly reduced the arterial expression of pro-inflammatory enzymes like COX-2 and prooxidant enzymes like NOX-4. Similarly, other authors have reported that both omega-3 and MUFA fatty acids supplementation exerts antioxidant and anti-inflammatory effects in arterial cells or tissue [ 79 , 83 ].…”
Section: Discussionmentioning
confidence: 71%
“…The doses used were representative of the nontoxic and effective range of NCM 1921 based on previous reports about individual components of NCM1921 (n-3 PUFA, caprylic, lauric acid, etc.) [18][19][20]. The severity of dermatitis and the clinical index of dermatitis were assessed according to a previously reported method [21].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Recently, a ratio of EPA : DHA 6 : 1 has been recognized as a potent formulation to improve endothelial functions in different studies. Intake of omega-3 formulation EPA : DHA 6 : 1 can restore endothelium-dependent NO-mediated relaxations, most likely, by preventing the upregulation of the local angiotensin system, NADPH oxidase, and the subsequent formation of ROS in old rats [ 218 ]. Also, EPA : DHA 6 : 1 can prevent endothelial senescence in middle-aged or old rats by limiting both the shedding of endothelial microvesicles and their prosenescent, prothrombotic, and proinflammatory effects in endothelium [ 218 ].…”
Section: Diet Effect On Endothelial Function and Oxidative Stressmentioning
confidence: 99%